ASUPAN VITAMIN D DAN PAPARAN SINAR MATAHARI PADA ORANG YANG BEKERJA DI DALAM RUANGAN DAN DI LUAR RUANGAN - Rimahardika, Rosita; Subagio, Hertanto Wahyu; Wijayanti, Hartanti Sandi (Journal of Nutrition College, 2017)
Background: The high deficiency of vitamin D were caused by low vitamin D intake which are limited amounts of vitamin D food sources, and sunlight exposure. Indoor workers were likely to be lower sunlight exposure, while outdoor workers were higher of sunlight exposure, but when someone often exposed sunlight used covering clothes and sun protector then the exposure was not enough to complete the needs of vitamin D. The purpose of this study was to compare intake of vitamin D and sunlight exposure between indoor and outdoor workers.Methods: The analytic descriptive study was held in Sayung Subdistrict with 60 sample aged 19-64 years were selected by using consecutive sampling. Vitamin D intakes was measured by SQ-FFQ and analyzed using nutrisurvey. Sunlight exposure were obtained by doing direct interview with questionnaire and sunlight exposure recall 3x24h. The data were analyzed by using descriptive tests and bivariate tests.Results: The indoor worker’s frequency of sunlight exposure was higher (p = 0.001), indoor worker’s body was more closed (p = 0.02), indoor worker’s habit of using sunlight protector was more often (p = 0.001), outdoor worker’s total duration of sunlight exposure was higher (p = 0.001), outdoor workers were more often to use polyester material textile (p= 0.07), and vitamin D intake was higher in outdoor workers than indoor workers (p = 0.79).   Conclusion: Indoor workers were at higher risk of vitamin D deficiency due to low vitamin D intake and sunlight exposure because of often used covering clothes and sunlight  protectors.